Honour and debt release in the parable of the Unmerciful Servant (Mt 18:23–33): A social-scientific and realistic reading - Eck, Ernest van (HTS teologiese studies, 2015)
This article presents a social-scientific and realistic reading of the parable of the Unmerciful Servant. The parables of Jesus are realistic stories about everyday events in 1st-century Palestine that evoke specific social realia and practices known to its first hearers. As recent studies on the parables have shown, papyri from early Roman Egypt provide detailed information on the implied social realities and practices assumed in the parables. In reading the parable through the lens of patronage and clientism and against the background of the relationship between royal ideology and debt release attested in documented papyri, it is argued that the parable suggests that in the basileia of God debt should be released in terms of general reciprocity, emulating the way in which patrons release debt for the sake of honour.